Influence of N and P fertilizer application on root growth, leaf photosynthesis and yield performance of groundnut (Bangladesh Journal of Agricultural Research, 2008)
Field experiments were carried out at the Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur during 2000-2002 to evaluate the effect of N and P applicaiton on the root growth, leaf photosynthesis and yield of groundnut (var. Basantibadam). Four levels of N (0, 20, 40 and 60 kg N/ha) and four levels of P (0, 13, 26 and 39 kg P/ha) were the treatment variables. The trial was set up in a randomized complete block design under factorial arrangement with three replications. Application of N and P fertilizer exerted significant effects on root development, photosynthesis, yield contributing characters and pod yield of the crop. Plant receiving 60 kg N and 39 kg P/ha had larger root system, greater photosynthetic rate and better yield contributing characters that resulted in the maximum pod yield which, however, was not significantly different from N60P26 treatment. Hence, it is recommended that higher yield of Basantibadam can be obtained from N60P26 kg/ha in salna silty clay loam soil of Madhupur tract (AEZ 28) of Bangladesh.DOI: http://dx.doi.org/10.3329/bjar.v32i3.538Bangladesh J. Agril. Res. 32(3) : 369-374, September 2007